Diversity of primates in Ayer Hitam Forest Reserve, Puchong, Selangor - Ahmad Juffiry, Shahidin; Yusof, Ebil; Hussin, Mohamed Zakaria (Faculty of Forestry, Universiti Putra Malaysia, 2013)
The two main factors that are known to affect the primate diversity and abundance in a forest are habitat structure and anthropogenic disturbance. However, many primate researchers had focused their study in contiguous lowland forests rather than isolated forests. This study examined the diversity of the primates in an isolated forest, i.e. the Ayer Hitam Forest Reserve (AHFR) in Puchong. Higher species richness, diversity and composition may contribute AHFR ecosystem to function more efficiently and productively. The Distance Sampling Method through line transects and opportunistic surveys were used to assess the abundance and diversity of primate species. Results of this study indicated that only four primate species were found in the AHFR out of a total of ten species present in Peninsular Malaysia. A total of 66 observations were recorded from the end of November to the end of December 2005. The density of primates at AHFR (all species) was 2.8 individuals/ha. Despite the limited size of the forest area and the level of disturbances, the diversity of primate species found remains high but the density is relatively low compared to other forested areas in Peninsular Malaysia.